Estimating Oil Reservoir Permeability and Porosity from Two Interacting Wells - S. Sutawanir; Agus Yodi Gunawan; Nina Fitriyati; Iskandar Fahmi; Anggita Septiani; Rini Marwati (Institute for Research and Community Services (LPPM) ITB, 2013)
The Ensemble Kalman Filter (EnKF) can be used as a method to estimate reservoir parameters, such as permeability and porosity. These parameters play an important role in characterizing reservoir performance. The EnKF is a sequential estimation method that uses the parameters at t